Mutual Interdependency between China, India and Nepal - Kathet, Gunja (Interdisciplinary Journal of Management and Social Sciences, 2021)
Due to geographical proximity and historically long multi-faceted linkages between China, India and Nepal their foreign policy with each other is not distinctly independent but is mutually interdependent. This paper argues that Nepal's foreign policy has always prioritized maintaining balanced relation with these two nations for safeguarding its national interests, integrity and independence. While doing so it will also shed light upon how Nepal has age old and deep rooted relations between both China and India whereupon Nepal-China and Nepal-India relations have evolved through different circumstances, stages and periods till date.